Six new species of Macellicephala (Annelida: Polynoidae) from the Southern Ocean and south Atlantic with re-description of type species - Neal, Lenka; Brasier, Madeleine J.; Wiklund, Helena (Zootaxa, 2018)
Increased sampling efforts in unexplored regions of the Southern Ocean (including depths >500 m) combined with the use of an epibenthic sledge resulted in a large collection of mobile, scale-bearing worms from the family Polynoidae Kinberg, 1856. The greatest taxonomic novelty was found in the genus Macellicephala McIntosh, 1885, the type genus of the exclusively deep-sea polynoid sub-family Macellicephalinae Hartmann-Schröder, 1971. Recently collected material from the Amundsen Sea led to discovery of four new species based on morphology and COI, 16S and 18S genes—Macellicephala gloveri sp. nov., M. linseae sp. nov., M. patersoni sp. nov. and M. brenesorum sp. nov. The holotype of type taxon Macellicephala mirabilis McIntosh, 1885 as well as historic material of Macellicephala collected from the Southern Ocean enabled comparison with the modern material. As a result, Macellicephala mirabilis is re-defined, and two new species, M. monroi sp. nov. and M. macintoshi sp. nov., are erected from the historic material previously ascribed to M. mirabilis. Additionally, DNA-suitable specimens assigned to M. monroi sp. nov. were collected from the Scotia Sea. Genetic data enabled the first test of the monophyly of Macellicephala. Based on current taxa coverage, these taxa form a well-supported monophyletic group as recovered by Bayesian and Maximum Likelihood analyses of our combined genetic dataset. In addition, the analysis shows strong support of a clade comprising Macellicephala and other exclusively deep-sea groups (including cave-dwelling taxa).